ALGORITHMS OF CONTROLLING AN INFORMATION ROBOT CREATED ON THE BASIS OF UNMANNED AERIAL VEHICLES - Tachinina, Olena; Lysenko, Alexander (Proceedings of National Aviation University (archive), 2020)
Purpose: The purpose of this article is to present the algorithms of control of unmanned aerial vehicles (UAVs) as part of the information robot. Methods: The article considers the method of the theory of optimal control of dynamic systems, which was used to stabilize the UAV on a given trajectory, taking into account a possible change in the purpose of the movement. Results: The first algorithm allows: to estimate the coordinates of the UAVs current position relative to a given trajectory; to develop the optimal control of the UAVs movement to a specified position taking into account a predetermined quality criterion; as well to identify the optimal points in time for the UAVs group maneuvering. The second one allows to stabilize the UAVs on a given trajectory, taking into account the possible change of the target movement at each time point on a selected interval, and to calculate the optimal time point and phase coordinate of the UAVs group separation. Discussion: The proposed algorithms will allows, depending on the course of events, to promptly optimize the UAVs trajectories and redirect them to the required emergency zone in order to obtain accurate operational data about the victims, as well as to coordinate the actions of rescue teams.